Market Structure and Cost Efficiency in China Banking Sector - Ye, Fengting (2016)
Abstract This paper adopts the SFA to investigate China banking sector (including Mainland, Hong Kong and Macau commercial banks) cost efficiency and scale economies condition. We find that China banks have the average cost efficiency at 94.8%, but Mainland has the average cost efficiency score at 97.8% and Hong Kong &Macau banks average at 88.9%. Then we find different bank categories have different cost efficiencies. As similar as in scale economies, on average, China banking sector is operating under scale economies. However, under the separate considerations, Mainland commercial banks are in scale economies but HKMO banks are scale diseconomies. Then, we examine the market share and bank size influences on bank cost efficiency and find that the market structure factors have significant effects on cost efficiency. Similarly, under separate frontier, the influences on HKMO banks become insignificant. According to results, we suggest that Mainland commercial banks can enhance cost efficiency level through changing banking market structure, but that does not make sense on HKMO commercial banks.